COMPARISON OF TREATMENT EFFICACY IN PAROXYSMAL ATRIAL FIBRILLATION - V. G. Tregubov; M. A. Eremina; S. G. Kanorsky; V. M. Pokrovsky (Кардиоваскулярная терапия и профилактика)
Aim. To compare efficacy of nebivolol (Nb) and sotalol (St) in patients with paroxysmal atrial fibrillation (AF) at the background of arterial hypertension (AH) and\or coronary heart disease (CHD), taken the influence on “regulatory-adaptive status” (RS).Material and methods. Totally, 60 patients included, with paroxysmal AF and AH of II-III stages and/or CHD, randomized to 2 groups for treatment with Nb (n=30) — 6,5±1,5 mg daily, or St (n=30) — 156,0±35,2 mg daily. In combination therapy, lisinopril was added — 13,4±3,7 and 13,3±4,0 mg daily, respectively, and if indicated — atorvastatin (n=10) 16,8±4,5 mg daily and (n=13) 16,3±4,9 mg daily, and acetylsalicylic acid — (n=14) 91,1±17,2 mg daily (n=12) 91,7±14,4 mg daily, respectively. At the baseline and in 6 months of therapy, the assessment was done: quantitative RAS by the tests of cardiac-respiratory synchronicity, echo, triplex brachiocephalic scan, treadmill test, 6-minute walking test, ambulatory blood pressure monitoring, ECG, subjective life quality assessment.Results. Both schemes of combination therapy were comparably sufficient for structural and functional condition of the heart improvement, with control over hypertension, and effectively suppressed the paroxysms of atrial fibrillation, and improved life quality. Also, Nb positively influenced RS and better increased exercise tolerance.Conclusion. In paroxysmal AF patients with AH of II-III stages and/or CHD, Nb as a part of combination treatment might be more preferred due to positive influence on RS, comparing to St.